Predictors of Nonroutine Discharge Disposition Among Parasagittal and Parafalcine Meningioma Patients. (16th November 2020) - Jimenez, Adrian; Khalafallah, Adham M; Huq, Sakibul; Horowitz, Melanie; Azmeh, Omar; Lam, Shravika; Oliveira, Leonardo; Brem, Henry; Mukherjee, Debraj
Abstract: INTRODUCTION: Discharge disposition is an important outcome for neurosurgeons to consider in the context of high-quality, value-based care. There has been limited research into how the unique anatomical considerations associated with parasagittal/parafalcine meningioma resection may influence discharge disposition. METHODS: 115 patients treated at a single institution were analyzed (2016-2018). Bivariate analysis was conducted using the Mann-Whitney U and Fisher's exact tests. Multivariate analysis was conducted using logistic regression. 5-fold cross-validation followed by receiver operating characteristic (ROC) curve analysis was used to assess logistic regression model performance. RESULTS: Our cohort was majority female (71.2%) and Caucasian (76.6%), with a mean age of 58.17 years. The majority of patients had tumors associated with the middle third of the superior sagittal sinus (SSS, 60.4%) and had tumors that were not fully occluding the SSS (69.4%). In multivariate analysis, independent predictors of nonroutine discharge disposition included mFI-5 score (odds ratio [OR] = 2.91, P = .0067), tumor size (OR = 1.04, P = .040), Simpson grade IV resection (OR = 5.45, P = .030) and occurrence of any postoperative complication (OR = 4.51, P = .047). CONCLUSION: In our single-institution experience, neither extent of SSS invasion nor location along the SSS predicted nonroutine discharge, suggesting that tumor invasion and posterior location of the SSS are not necessarily contraindications to surgery. Our results also highlight the importance of frailty and tumor size in stratifying patients at-risk of nonroutine discharge disposition.